Increased Gene Expression of RUNX2 and SOX9 in Mesenchymal Circulating Progenitors Is Associated with Autophagy during Physical Activity. (15th October 2019) - Dalle Carbonare, L.; Mottes, M.; Cheri, S.; Deiana, M.; Zamboni, F.; Gabbiani, D.; Schena, F.; Salvagno, G. L.; Lippi, G.; Valenti, M. T.
Abstract : Lack of physical exercise is considered an important risk factor for chronic diseases. On the contrary, physical exercise reduces the morbidity rates of obesity, diabetes, bone disease, and hypertension. In order to gain novel molecular and cellular clues, we analyzed the effects of physical exercise on differentiation of mesenchymal circulating progenitor cells (M-CPCs) obtained from runners. We also investigated autophagy and telomerase-related gene expression to evaluate the involvement of specific cellular functions in the differentiation process. We performed cellular and molecular analyses in M-CPCs, obtained by a depletion method, of 22 subjects before (PRE RUN) and after (POST RUN) a half marathon performance. In order to prove our findings, we performed also in vitro analyses by testing the effects of runners' sera on a human bone marrow-derived mesenchymal stem (hBM-MSC) cell line. PCR array analyses of PRE RUN versus POST RUN M-CPC total RNAs put in evidence several genes which appeared to be modulated by physical activity. Our results showed that physical exercise promotes differentiation. Osteogenesis-related genes as RUNX2, MSX1, and SPP1 appeared to be upregulated after the run; data showed also increased levels of BMP2 and BMP6 expressions. SOX9, COL2A1, and COMP gene enhanced expression suggested the induction of chondrocytic differentiation as well. The expression of telomerase-associated genes and of two autophagy-related genes, ATG3 and ULK1, was also affected and correlated positively with MSC differentiation. These data highlight an attractive cellular scenario, outlining the role of autophagic response to physical exercise and suggesting new insights into the benefits of physical exercise in counteracting chronic degenerative conditions.